2017
DOI: 10.1002/anie.201701223
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biosynthesis of Isatropolones, Bioactive Amine‐Scavenging Fluorescent Natural Products from Streptomyces Gö66

Abstract: The natural products isatropolone A-C (1-3) were reisolated from Streptomyces Gö66, with 1 and 3 showing potent activity against Leishmania donovani. They contain a rare tropolone ring derived from a type II polyketide biosynthesis pathway. Their biosynthesis was elucidated by labeling experiments, analysis of the biosynthesis gene cluster, its partial heterologous expression, and structural characterization of various intermediates. Owing to their 1,5-diketone moiety, they can react with ammonia, amines, lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…A monoacylated molecule with m/z 513.2 ([M-H] - ) was detected in the extract, which was isolated through a sequence of chromatographic steps to yield 5 mg of purified compound. Single and 2-dimensional NMR spectroscopic data (Supplementary Table S4 and Supplementary Figures S3 – S7 ) for the compound was consistent with a O -acylated derivative of the recently described Isatropolone C ( Figure 4 ) ( Cai et al, 2017 ). The absorbance spectrum (Supplementary Figure S2 ) revealed distinct maxima at 300–350 nm and closely resembled the spectrum reported for Isatropolone A ( Cai et al, 2017 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A monoacylated molecule with m/z 513.2 ([M-H] - ) was detected in the extract, which was isolated through a sequence of chromatographic steps to yield 5 mg of purified compound. Single and 2-dimensional NMR spectroscopic data (Supplementary Table S4 and Supplementary Figures S3 – S7 ) for the compound was consistent with a O -acylated derivative of the recently described Isatropolone C ( Figure 4 ) ( Cai et al, 2017 ). The absorbance spectrum (Supplementary Figure S2 ) revealed distinct maxima at 300–350 nm and closely resembled the spectrum reported for Isatropolone A ( Cai et al, 2017 ).…”
Section: Resultssupporting
confidence: 81%
“…Disk diffusion assays clearly indicated that a highly active compound (or compounds) are produced by Streptomyces A1RT. A prominent compound produced by Streptomyces A1RT was purified and spectroscopically shown to be Isatropolone C. Isatropolone C was recently discovered as a metabolite of Streptomyces Gö66 and was shown to have anti-parasitic activity ( Cai et al, 2017 ). In our study, we report that an Isatropolone C containing extract shows high antibiotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…7 Aer the tropolone alkaloid rubrolone A produced by Streptomyces enchinoruber was rst reported in 1978 ( Fig. 1B), 8 the rubrolone family has since expanded with the identication of isatropolones 9 and rubterolones 10 from Actinomycete strains (Fig. 1B).…”
Section: Introductionmentioning
confidence: 92%
“…The unknown metabolites were then purified by a combination of chromatographic methods, and Proposed functions for individual ORFs have been reported previously. [7,10] C) Structures of compounds 1-6 and ORTEP representation of 2 a and enantiomer 4 a (A pair of selected enantiotopic X-ray structures of 4 a from one crystal cell).…”
Section: Heterologous Expression Of Cosmid P10c7 Accumulates Tropolon...mentioning
confidence: 99%
“…These tropolonoids exhibit anti‐bacterial, anti‐fungal, and anti‐inflammatory properties, and have also been demonstrated to act as promising candidates for the induction of autophagy [9] . Further to the highly promising therapeutic utility of the isarubrolones, various aglycone subunits from this family can be used as probes for the covalent labeling and visualization of molecules containing and amine functionality [7] . In a previous study, we cloned and sequenced the rubrolone biosynthetic gene cluster (BGC) from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%